Development of agricultural holdings in Ukraine in the process of reorganisation of agriculture of the XXI century - Janina Fedorenko (Cхід, 2013)
The article is devoted to the research of history of the process of agricultural holdings forming and activity, determining their place and role in the agricultural sector of the ХХІ century. Besides, laws and regulations formed in the end of 1990-s - beginning of 2000-s, that regulated the process of forming and functioning of these agricultural market operators, were given characteristic to. Background, scheme and three stages of agricultural holdings formation (І - 2000-2005 years, ІІ - 2006-2009 years, ІІІ - 2010-2011 years,) were analyzed Their structure, peculiarities of zoning and production field of concern of these leading agricultural market operators were defined. Specificity of their activity in different phases of history, especially under conditions of moratorium in 2001, crisis of 2008 and 2009-2011 is researched. Attention is paid to the functioning of the largest enterprises, namely agricultural holdings "Ukrlandfarming", "Kernel Holding" and "Mrija Agroholding". Three approach directions of agricultural holdings to the agricultural areas development are studied. According to our research data, logical conclusions are made where the author estimated dually the role of agricultural holdings under the conditions of Ukrainian village reform. On the one hand, they well take care of the object of their management - farmland, using the newest technologies for their cultivation, and for many villagers they offer real employment. Nevertheless, on the other hand, majority of agricultural holdings do not pay any attention, (especially, financial) to the rural development, on the contrary, they add to Ukrainian village infrastructure ruining.